Implementasi Tata Kelola Perusahaan Terhadap Nilai Perusahaan: Studi Empiris pada Perusahaan di Indonesia - Patricia Diana (Universitas Multimedia Nusantara, 2015)
Indonesia as one of developing countries should prepare for intense business competition in international market by continuously improving their financial performance which reflected by profitability enhancement. In order to achieved this goals, companies should build synergic relationship between stakeholders. Implementation of corporate governance is believed can assist companies in improving firm value by minimizing cost and maximize companies’ profit. This study aims to investigate the effect of corporate governance implementation on Indonesian companies. Corporate Governance Perception Index (CGPI) which establish by Indonesian Institute of Corporate Governance (IICG) used as proxy for corporate governance implementation, and ROA used as proxy for firm value. All the data obtain from Indonesia Stock Exchange (IDX) database and period 2008 to 2012 used as observation period. The result show that implementation of corporate governance has significant effect with firm value proxy by ROA. This study also concludes that market will be more concern on CGPI which generated through documentation and presentation indicators and also observation indicators rather than self-assessment indicators. This indicates that market would trust the information which comes from independen external parties. The result will be useful for investor in making their investment decision which based on profitability consideration. Keywords: Corporate Governance, CGPI, ROA, profitability